Pendampingan dan Pelatihan Pola Pembelajaran Digital bagi Tenaga Pendidik di SDN 41 Pangkalpinang - Dian Prihardini Wibawa; Nizwan Zukhri; Dini Oktariani; Muhamad Hijran; Tsulis Amirudin Zahri; Indah Noviyanti (Prima Abdika : Jurnal Pengabdian Masyarakat, 2022)
Assistance and training on digital learning patterns for educators at SDN 41 Pangkalpinang is carried out using the workshop method. The speaker has prepared the material to be delivered related to digital learning, then the teaching staff is directed by the community service team to simulate the material that has been delivered by the presenter. This program aims to improve the skills of educators in using digital learning such as using Zoom, Google Meet, Google Classroom and using interactive quizzes using platforms such as Wirldwall so that it can be done in hybrid learning. The results of this mentoring and training received positive appreciation from educators that they can implement effective and efficient digital learning.